INDOGLISH USED BY MOBILE LEGENDS PLAYERS ON INSTAGRAM - Dina Fitri, Dwi; Tahrun; Ana Theriana (Esteem Journal of English Education Study Programme, 2024)
This study investigates the use of Indoglish a mix of Indonesian and English  as a sociolinguistic phenomenon among Mobile Legends players on a social media with around 56% Indonesian population are using named Instagram. Involves the integration of Indonesian linguistic elements with English vocabulary through qualitative methods: observations, interviews and documentation. The formation likely English nouns and adjectives with Indonesian prefixes (di-, nge-, se-) and suffixes (-nya, -an).  Prominent Indoglish phrases like "partyan," "matchmakingnya," "ditroll/ngetroll," "ngebug," "ngepush," "ngerank," "systemnya," "segame," "skillnya," "ngelag," "gamenya," and "ngestuck" are found and examined based on informants also players’ feedback. The results demonstrate that gamers often use Indoglish phrases on Instagram and in game, demonstrating how skilledly they can use these terms. Gamers believe that Mobile Legends is a useful tool for improving their English in a variety of settings, supporting Indoglish since it is useful and accepting of its contribution to improving their relationships with other players.